Incidentally Found Prostate Cancer and Influence on Overall Survival after Radical Cystoprostatectomy. (22nd April 2012) - Sruogis, Algimantas; Ulys, Albertas; Smailyte, Giedre; Kardelis, Zygimantas; Kulboka, Arunas; Anglickienė, Giedre; Samalavicius, Nerimantas; Anglickis, Marius
Abstract : Objectives . To determine incidentally found prostate cancer frequency and impact on overall survival after RCP. Patients and Methods . The records of 81 men who underwent cystoprostatectomy from January 2000 to December 2009 were reviewed. The vital status of the study group was assessed as on September 1, 2009, by passive followup, using data from the population registry. Results . The 81 men underwent RCP. The incidental prostate cancer was found in the specimens of 27 (33.3%) patients. 13 (48.1%) of 27 prostate cancer cases were clinically significant. For 3 patients (11.1%) an extraprostatic extension was found. For 2 patients (7.4%)—positive margins, for 1 patient (3.7%)—Gleason sum 8, and for the rest 7 patients bigger than 0.5 cm 3 volume tumor, and Gleason sum 7 was found. The mean follow-up time was39.2 ± 33.8 months (varies from 0.8 to 131.2 months). The patients with bladder cancer and incidentally found prostate cancer lived shorter (28.1 ± 27.5 and45.5 ± 35.40 months). Higher overall survival (P = 0.03 ) was found in the patient group with bladder cancer without incidentally diagnosed prostate cancer. Conclusion . There are indications that in this small study prostate cancer has influenced on patients' survival with bladder cancer after radical cystoprostatectomy.